Cajamarca carnival coplas, stereotypes of women and underlying gender - Quintana Peña, Alberto Loharte (2020)
In order to demonstrate whether automated content analysis can be effective for the identification and analysis of social representations, around three thousand couplets sung at the Cajamarca carnival were collected and analyzed with the software for Text Analysis, T -Lab, seeking to identify the social representations present in them. Finding that in the male representations a role play is shown that the genders would assume, in which a woman must be young and beautiful, to offer her body in exchange for the money that the man should provide, denoting the dominance of the man over the woman and the tendency to ideological devaluation of the latter. On the contrary, in the female representation a romantic vision of the couple is evident. Sexist representations in the carnival songs of Cajamarca became evident. In both representations of both men and women, when referring to the subjects of their rejection attitudes, they allude to their ethnic origin, denoting a racist ideology of ideological devaluation of the original population.